More than mere playthings : the minor arts of Italy - Fischer, Julia C. (Cambridge Scholars Publishing, 2016)
This book is inspired by the 2015 Italian Art Society-sponsored conference sessions of the American Association of Italian Studies. Its seven chapters span the art of ancient Etruria to twentieth century Italy, and explore a variety of media, including mirrors, cameos, treasury objects, reliquaries, ceramics, and figurines. Contributors approach the topic of the minor arts from a variety of interdisciplinary perspectives, including reception, use, patronage, gender issues, propaganda, and iconography. The volume thus fills the lacuna in the scholarship of the minor arts, and reveals that the minor arts are unique and worthy of study for their size, preciosity, patronage, audience, function, portability, and material. Ultimately, in revealing the importance of these objects, the book shows that the division between the major and minor arts is no longer valid, and that these objects of the minor arts hold as much significance as those of the major arts.